Implementation of School Cultural Management in Forming Religious Character at MTS Ar-Rahmah Kediri - Salsabila Nur Hamiidah; M Taufiqurrohma; Sumedi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
A strong approach to the formation of religious character in schools can indeed be reflected through the school culture implemented. School culture is a characteristic of every school that only each school has. So it's no wonder every school has different rules. This study aims to find: 1). The form of school culture programs in building religious character, 2). The implementation of school culture in building religious character, 3). The impact of the success of school culture in building religious character. This research uses a qualitative approach with a descriptive type. This research was conducted at MTa Ar-Rahmah Kediri. Data analysis used by researchers is data collection, data reduction, data presentation, and conclusions. The results of this study are known that: 1). The form of school culture programs in building the religious character of participants carried out with 6S such as cultured manners, amaliah dhuha, tahlil, reading the Qur'an, focuses on fundamentals. 2). Implementation of school culture in building the religious character of students through Islamic values, Islamic activities, and Islamic symbols. 3). The successful implementation of school culture in building the religious character of students has a significant and increasing impact on students, teachers, and staff on the school.